Serological markers of gluten sensitivity in Border terriers with gall bladder mucocoeles. (26th August 2020) - Barker, L.; Tivers, M. S.; Kathrani, A.; Allerton, F.; Powell, R.; Stam, L.; Black, V.
Abstract : Objectives: To evaluate serological markers of gluten sensitivity in conjunction with cholecystokinin measurement in Border terriers with gall bladder mucocoeles. Materials and Methods: Medical records from two referral hospitals were obtained between 2011 and 2019 to identify Border terriers with gall bladder mucocoeles, non‐Border terriers with gall bladder mucocoeles and control Border terriers with non‐biliary diseases. Enzyme‐linked immunosorbent assays were performed on stored fasted serum samples for anti‐gliadin IgG, anti‐canine transglutaminase‐2‐IgA autoantibodies and cholecystokinin. Statistical analysis was performed using the Kruskall‐Wallis test to identify differences between the groups. Results: Fifteen Border terriers with gall bladder mucocoeles, 17 non‐Border terriers with gall bladder mucocoeles and 14 control Border terriers with non‐biliary diseases were recruited. Median transglutaminase‐2‐IgA autoantibodies in Border terriers with gall bladder mucocoeles was 0.73 (range: 0.18 to 1.67), which was significantly greater than in control Border terriers at 0.41 (0.07 to 1.14). Median cholecystokinin concentration in Border terriers with gall bladder mucocoeles was 13 pg/mL (6 to 45 pg/mL), which was significantly lower than in control Border terriers at 103 pg/mL (9 to 397 pg/mL). There was no difference in the anti‐gliadin IgG between these groups. There was no difference observed in the non‐Border terriers with gall bladder mucocoeles with either of the other groups. Clinical Significance: Reduced cholecystokinin and increased transglutaminase‐2‐IgA autoantibodies was detected in Border terriers with gall bladder mucocoeles; which is in part homologous to gall bladder disease identified in human coeliac disease. The results suggest an immunological disease with impaired cholecystokinin release may be affecting gall bladder motility and possibly contributing to mucocoele formation in Border terriers.